Unlocking Africa's Agricultural Potential - World Bank (Washington, DC, 2014)
Transforming agriculture in Africa is not simply about helping Africa; it is essential for ensuring global food security. But Africa s agriculture is also of critical importance when it comes to meeting the world s future needs for food and fiber. With the global population expected to exceed 9 billion by 2050, food security producing enough food of sufficient quality and making it accessible and affordable for consumers around the world is one of the most important policy objectives .The United Nations estimates that global food demand will double by 2050, with much of that growth driven by developing countries. The world will then need to feed 2.3 billion more people, and given the deep transformation of growth trajectories in low-income countries, these populations will be increasingly affluent and will demand more, different, and better food. But how will the world meet this additional demand? Given Africa s productive potential, it must be a key contributor to feeding the world in the future. But to fully realize that potential will require overcoming many obstacles through innovative and transformative approaches.